Effects of Transient Thermal Shock on the Microstructure and Mechanical Properties of CoCrFeNiMn High-Entropy Alloy Coatings - Liu, Jing-Tong; Liu, Si-Wei; Zheng, Hai-Lan; Huang, Wen-Jing; Zhao, Wei; Liao, Wei-Bing (Frontiers in Materials, 2021)
CoCrFeNiMn high-entropy alloy (HEA) has great potential for engineering application due to its good ductility and high fracture toughness at low temperature. It can be deposited on components as coatings to take advantage of its excellent properties and reduce the cost. In this study, CoCrFeNiMn HEA coatings were deposited on 316L stainless steel substrates by atmospheric plasma spraying (APS) technique, and a series of transient thermal shock tests were performed. It was found that the coatings contained two main phases: a face-centered cubic (FCC) solid solution phase and a flocculent oxides phase. The elemental contents of Co, Cr, Fe, and Ni were close to equal atomic percentage in the coating, while Mn was reduced significantly. The oxygen was mainly distributed in the dark flocculent oxides phase. After transient thermal shock tests, these two phases remained stable, but some tiny cracks appeared on the surface. Meanwhile, the microhardness of the coating after transient thermal shock tests also showed stable, 420 HV. Weibull statistics were used to analyze the reliability of the microhardness, and the Weibull modulus m was distributed from 9 to 15. The CoCrFeNiMn HEA coating exhibited high phase stability and excellent properties under transient thermal shock, making it have service advantages in extreme environments, especially in the fields of the development of future nuclear and aerospace structural materials.